International support for abortion education in medical schools: results of a global online survey to explore abortion willingness, intentions, and attitudes among medical students in 85 countries - Janušonytė, Eglė; Fetters, Tamara; Cipriano, Gabriela; Jemel, Iheb; Espinoza, Cecilia (Frontiers in Global Women's Health, 2024)
Access to safe abortion has been recognized as a fundamental human right and important public health priority. Medical schools provide a rare opportunity to expose medical students to comprehensive sexual and reproductive health (SRH) topics and normalize abortion care early in a physician's career. This cross-sectional descriptive study used an online survey to explore abortion content in medical curricula and medical student intentions, attitudes, and beliefs regarding abortion provision among 1,699 medical students from 85 countries. Results demonstrate positive attitudes towards abortion provision, with 83% reporting that "access to safe abortion is every woman's right". Students also reported a relatively high willingness to provide abortion professionally despite few opportunities to learn about this care. Only onethird of students surveyed reported having taken a gynecology course (n=487; 33%); among these, one-third said they had no content on abortion care in their programs thus far (n=155; 32%), including instruction on postabortion care. Among the two-thirds of students who had some content on abortion care (n=335), either on induced abortion, postabortion care (PAC), or both, 55% said content was limited to one lecture and only 19% reported having an opportunity to participate in any practical training on abortion provision. Despite most students having no or very limited didactic and practical training on abortion, 42% intended to provide this care after graduation. Three-quarters of student respondents were in favor of mandatory abortion education in medical curricula. The findings of this study offer new evidence about abortion care education in medical curricula around the globe, indicating that there is no lack of demand or interest in increasing medical knowledge on comprehensive abortion care, merely a lack of institutional will to expand course offerings and content.